Real-time PCR method for the quantitative analysis of human T-cell receptor γ and β gene rearrangements - Chain, J.L. (2005)
Analyzing the status of T-cell receptor (TCR) gene rearrangements has been an essential part of deciphering the stages of thymocyte development, understanding the αβ vs. γδ lineage decision, and characterizing T-cell leukemias. Methods such as PCR and quantitative Southern blotting provide useful information, but also have significant shortcomings such as lack of quantitation in the case of PCR and technical challenges in the case of Southern blotting. Here we describe a real-time PCR method that overcomes many of these shortcomings. This new method shows comparable results for the fraction of unrearranged TCRγ and TCRβ genes in human thymocytes and peripheral blood T cells as Southern blotting, and has the advantages of being simple to perform, highly quantitative, and requiring nanogram quantities of DNA. We also describe a real-time PCR method to quantitate T-cell receptor excision circles formed during TCRβ rearrangements.